Mimbres during the twelfth century : abandonment, continuity, and reorganization - Nelson, Margaret Cecile, 1951- (Book collections on Project MUSE., 1999)
By examining the economic and social reasons for change among the Mimbres, Nelson reconstructs a process of shifting residence as people spent more time in field camps and gradually transformed them into small hamlets while continuing to farm their old fields. Challenging current interpretations of abandonment of the Mimbres area through archaeological excavation and survey, she suggests that agricultural practices evolved toward the farming of multiple fields among which families moved, with small social groups traveling frequently between small pueblos rather than being aggregated in large villages.